The Effects of Innovations on Bank Performance: The Case of Electronic Banking Services - TUNAY, KAŞİF BATU; TUNAY, NECLA (ELSEVIER SCIENCE BV, 2015)
In this study, we investigated the effects of the bank's profitability performance of electronic-based banking services. The effects of ROA and ROE performance were analyzed the data, which are 23 developed and developing countries' electronic banking services through 2005 to 2013, by dynamic panel data methods. Due to the innovative nature of electronic banking services will show the bank performance significantly. Both the analyzing method and involving of developed and developing countries' banking data are the most obvious differences of the study from similar studies in the literature. Result show that bank profitability of developed and developing countries affected from the ratio of the number of branches to the number of ATMs is highly significant and electronic banking services in significant. Results show that some variables were found to be in contrast to the expected negative relationship, because of diversity in the level of development of the countries, the socio-cultural structure and electronic banking infrastructure. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Innovation; elektronic banking; profitability; dynamic panel data; INTERNET BANKING